Hubungan Peran Orang Tua, Penggunaan Gadget Dan Kebiasaan Jajan Terhadap Perkembangan Emosional Anak Usia Pra-sekolah Di Pondok Pesantren Walisongo: The Relationship Between the Role of Parents, the Use of Gadgets and Snacking Habits on the Emotional Development of Pre-school Children at the Walisongo Islamic Boarding School - Sa’adah, Khalimatus (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: The pre-school period is a time when physical and psychological growth grows rapidly. The rate of delay in growth and development of children in Indonesia is still quite high, namely around 5-10% experiencing general developmental delays so it requires serious attention. Two out of 1,000 babies experience motor development disorders and out of 100 children have less intelligence and speech delays. The population of children in Indonesia reaches around 33% of the total population which is around 83 million and every year the number of children continues to increase. (Vitrianingsih et al 2018). Family is an important factor in child development. In addition, pre-schoolers need the role of parents in regulating their eating habits. Not only eating habits but snack habits also need attention. Another factor that is no less important is the use of gadgets in children. Children's behavior in using gadgets has both positive and negative impacts. (Imron 2018)  Methods: The research design used an analytic study with a cross-sectional approach.  Results: The chi-square test results show the value of the role of parents with a p-value (0,056) less than 0,5; use of gadgets p-value (0,17) less than 0,5; snacking habits p-value (0.131) less than 0,5; so the decision taken is to accept Ha. This means that there is a relationship between the role of parents, the use of gadgets, and snack habits on the emotional development of pre-schoolers at Walisongo Islamic Boarding School in 2023.  Discussion: It is recommended that schools hold parenting activities about the importance of controlling and supervising their children in the use of gadgets, providing counseling, and being able to involve student guardians to provide material or education regarding the consumption of balanced nutritious food.